Development of an Integrated Project-Based Learning Module Based on Black Soybean Ethnoscience to Improve Students' Science Process Skills - Dita Purwinda Anggrella; Ahmad Kamal Sudrajat (Jurnal Penelitian Pendidikan IPA, 2024)
Science process skills are one of the 21st-century skills that are important to optimize to train students to be skilled in solving problems. However, facts in the field show that science process skills are still relatively low because teachers do not yet understand how to develop science process skills, and there is a lack of teaching materials based on a scientific approach to developing science process skills. This research aims to develop an integrated Project-based Learning (PjBL) module for black soybean ethnoscience that is valid, practical, and effective for improving students' science process skills. The model for product development is ADDIE. The product's effectiveness was tested using a quasi-experiment with research subjects consisting of 91 students (46 experimental and 45 control group students). The results of the module developed meet valid and practical criteria. The results of product effectiveness tested using quasi-experiments show that the integrated PjBL module of black soybean ethnoscience effectively improves science process skills. They are increasing students' science process skills due to using contextual phenomena in learning.